Crossed Eye/Hand Laterality and Left-Eyedness Predict a Positive 24-Month Outcome in Alcohol-Dependent Patients - Weinland, Christian; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Alcoholism-Clinical and Experimental Research, 2019)
Background: Available predictors of hospital readmission following withdrawal in alcohol-dependent patients are limited. However, such parameters are needed to optimize individualized treatment strategies. This study investigated whether crossed eye/hand laterality, eyedness, and handedness may predict outcomes in alcohol dependence. Methods: The prospective study included 200 early-abstinent alcohol-dependent inpatients (n[males] = 113, n[females] = 87) and 240 control subjects (n[males] = 133, n[females] = 107). We assessed eyedness and handedness using the hole-in-the-card and Shimizu tests and documented alcohol-related readmissions over 12 and 24 months. Results: Crossed eye/hand laterality and left-eyedness were associated with a reduced risk for alcohol-related readmission (12-month: odds ratios [OR] = 0.41, p = 0.008, OR = 0.42, p = 0.004; 24-month: OR = 0.57, p = 0.097, OR = 0.47, p = 0.016), fewer median readmissions (12-month: 0 vs. 1, p = 0.005, 0 vs. 1, p = 0.005; 24-month: 1 vs. 2, p = 0.014, 1 vs. 2, p = 0.006), and more mean days to the first readmission (12-month: 270 vs. 209, p = 0.007, 269 vs. 207, p = 0.003; 24-month: 462 vs. 335, p = 0.039, 461 vs. 323, p = 0.005). They also interacted with treatment and alcohol drinking history to predict the outcome. In sex-specific analyses, most of these effects remained significant in males but not in females. Handedness alone did not significantly predict outcome. Moreover, the laterality markers did not significantly differ between alcohol-dependent patients and control subjects. Conclusions: Determining crossed eye/hand laterality and eyedness may help to individualize relapse prevention in the future. Both are easily accessible predictors of alcohol-related readmission following inpatient withdrawal treatment.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Alcohol Dependence; Crossed Eye/Hand Laterality; Eyedness; Relapse Prediction